KEMAMPUAN PENGGUNAAN KATA YANG DAPAT DIPISAHKAN OLEH MAHASISWA TINGKAT III STBA-PIA 亚院华文系三年级学生使用汉语离合词的能力考查 - Cynthia Hualangi (Journal of Language, Literature and Teaching, 2022)
This research aims to describe the ability of STBA-PIA Medan third-year undergraduates in using the separable words in Chinese language. Quantitative descriptive research is conducted on 40 students whom are both the population and sample through saturated sampling technique. The instrument created to collect the required data for analysis is a test with 25 questions. Content validity is utilised, and the reliability coefficient of each question in the instrument with KR-20 formula is 0.734, meaning the instrument has highly reliable. The result shows that the students' average ability in using the separable words in Chinese language is 65.3, indicating that they are not competent. Keywords: ability, separable words, Quantitative Research.